Eksistensi Kewenangan Legislasi Dewan Perwakilan Daerah Pasca Putusan Mahkamah Konstitusi Nomor 79/Puu-Xii/2014 - Harry Setya Nugraha (Universitas Muara Bungo, 2021)
The presence of the Constitutional Court's Decision Number 79/PUU-XII/2014 brought fresh air to the strengthening of DPD institutions. However, not a few parties still question the actual existence of the DPD in the Indonesian constitutional system, especially in terms of legislative authority. This article will try to discuss the existence of DPD legislative authority after the Constitutional Court Decision Number 79/PUU-XII/2014 and effective ways to strengthen the existence of DPD legislative authority in the Indonesian constitutional system. The methodology used is a normative juridical research method, with a statutory and conceptual approach, as well as a qualitative descriptive analysis. This article concludes that although the DPD legislative authority exists de jure through the Constitutional Court Decision Number 79/PUU-XII/2014, the de facto legislative authority of the DPD cannot be said to exist for two reasons. If the state is committed to strengthening the legislative authority of the DPD, then the constitutional steps that must be taken are not enough just to rely on the Constitutional Court's decision or by making changes to the MD3 Law. The thing that needs to be done is to formulate Article 22D of the 1945 Constitution of the Republic of Indonesia using diction which contains obligatory norms. The only way to reformulate the Article is by way of the Amendment to the 1945 Constitution of the Republic of Indonesia. Keyword: State Institution, DPD, Law Undang AbstrakHadirnya Putusan MK Nomor 79/PUU-XII/2014 membawa angin segar terhadap penguatan kelembagaan DPD. Namun begitu, tidak sedikit pihak masih mempertanyakan bagaimana sebenarnya eksistensi DPD dalam sistem ketatanegaraan Indonesia, khususnya dalam hal kewenangan legislasi. Artikel ini akan coba membahas soal eksistensi kewenangan legislasi DPD pasca Putusan MK Nomor 79/PUU-XII/2014 dan cara yang efektif untuk memperkuat eksistensi kewenangan legislasi DPD dalam sistem ketatanegaraan Indonesia. Metodologi yang digunakan adalah metode penelitian yuridis normatif, dengan pendekatan perundang-undangan, dan konseptual, serta analisis dilakukan secara deskriptif kualitatif. Artikel ini berkesimpulan bahwa meskipun secara de jure kewenangan legislasi DPD eksis melalui Putusan MK Nomor 79/PUU-XII/2014, namun secara de facto kewenangan legislasi DPD belum dapat dikatakan eksis oleh karena dua alasan. Jika negara berkomitmen untuk menguatkan kewenangan legislasi DPD, maka langkah konstitusional yang harus dilakukan tidaklah cukup hanya dengan bergantung pada putusan MK maupun dengan dilakukannya kembali perubahan terhadap UU MD3. Hal yang perlu dilakukan adalah merumuskan Pasal 22D UUD NRI 1945 dengan menggunakan diksi yang mengandung norma obligatoir. Satu satunya cara untuk merumuskan kembali Pasal tersebut adalah dengan cara Perubahan UUD NRI 1945.Keyword: Lembaga Negara, DPD, Undang-Undang